Strength and conditioning recommendations for female athletes: The Gaelic footballer - Duggan, J. D.; Keane, K.; Moody, J.; Byrne, P. J.; Malone, S.; Collins, K.; Ryan, L. (Strength and Conditioning Journal, 2023)
Ladies Gaelic football (LGF) is a traditional, amateur Gaelic sport played by female athletes. LGF is an invasion-based field sport involving high-intensity, intermittent match play. There is currently a paucity of research on intercounty (elite level) LGF despite a growing interest in the male version of the game. This article aims to provide strength and conditioning recommendations for LGF with particular focus on the intercounty level of play. Recommendations within this article include a needs analysis, female injury epidemiology, physical and physiological demands, female physiology, strength training, and specific conditioning guidelines based on the sport. Additional recommendations include an LGF-specific testing battery, a proposed periodization cycle, and sports-specific speed and agility development.